Analisis Kualitas Pelayanan Dan Fasilitas Stasiun Terhadap Kepuasan Penumpang MRT Jakarta - Devanka, Rizki Aulya (Institut Transportasi dan Logistik Trisakti, 2023)
Mass Rapid Transit or MRT is one of the most popular transportation facilities by residents in Jakarta and the outskirts of Jakarta because the MRT has comfortable and safe infrastructure and facilities. This research is a type of descriptive quantifiable research by taking a descriptive statistical approach. Done with the questionnaire method to MRT users as many as 100 respondents, namely someone who has used mrt Jakarta aged 15 years – 64 years, using the Purposive Sampling sampling technique and carried out with quantitative analysis including validity tests and reability tests, hypothesis tests, Multiple Linear Regression, Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). Based on the results of the study, it was found that the variables of Service Quality and Station Facilities have an influence on Passenger Satisfaction partially and simultaneously. The results of the analysis using the Customer Satisfaction Index (CSI) method showed that the level of passenger satisfaction with the quality of the Jakarta MRT was 90.8%, which means that this value is at a very satisfied level. This shows that passengers who use the Jakarta MRT are very satisfied with the performance and services provided by MRT Jakarta. The results of the analysis using the Importance Performance Analysis (IPA) method can be seen that of the 38 attributes assessed, there are 14 attributes that are in quadrant I. These attributes are the top priority to be improved by MRT Jakarta so that the level of passenger satisfaction is in accordance with the level of importance.